Habilidades sociais de crianças com diferentes necessidades educacionais especiais: comparações múltiplas - Freitas, Lucas Cordeiro (Universidade Federal de São Carlos, 2011)
Evaluation studies about social skills of children have shown that in general there is an impairment of social skills in learning disabilities, sensory disabilities and other conditions of special educational needs. However, there is a gap in the literature as to a broader comparison of social skills of a greater diversity of populations of children, including sensory disabilities, mental retardation, children with attention deficit hyperactivity disorder, autism, behavior problems, learning disabilities, among others. The paucity of comparative studies to evaluate children with different special needs has hindered the production of empirical knowledge about specific issues to each population. Moreover, the lack of comparative evaluation studies has been an obstacle to the identification of needs that might guide the goals of educational and therapeutic interventions in social skills among children with different developmental characteristics. This study aimed to fill part of this gap and its goals was: (a) to compare, based on teacher evaluation, the repertoire of social skills of children from 12 different groups of special educational needs among themselves and with the normative sample of the Social Skills Rating System- SSRS-BR (Autism, Hearing Impairment, Mild Mental Retard, Moderate Mental Retard, Visual Impairment, Phonological Disorder, Learning Disabilities, Giftedness and Talent, Externalizing Behavior Problems, Internalizing Behavior Problems, Internalizing and Externalizing Behavior Problems and Attention Deficit Hyperactivity Disorder), (b) identify resources and deficits in social skills from each of the 12 groups and (c) assess the degree of prediction of different special educational needs on the repertoire of social skills of the children. Teachers of 120 students in regular and special schools, aged between six and 14 years, from four states, responded to the SSRS-BR to assess the social skills of their students. The results showed that the special needs that had a lower frequency of social skills compared to the other were also the best predictor of deficits in this area, according to the regression analysis performed: ADHD, Autism, Internalizing and Externalizing Behavior Problems and Externalizing Behavior Problems. Furthermore, the groups that most often presented these skills were Gifted and Talented, Children with Visual Impairment and Mild Mental Retard. The comparative analysis identified resources and deficits in specific social skills to each of the 12 participating groups. The results were discussed in relation to the intervention needs of each population, providing possible educational and therapeutic implications.
Keywords: Habilidades sociais; Crianças; Educação especial; Problemas de comportamento; Dificuldades de aprendizagem; Avaliação psicológica; Professores; Social skills; Children; Special educational needs; Behavioral problems; Learning disabilities; Assessment; Teacher; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL